Number - Corbett, Greville G. (Cambridge textbooks in linguistics., 2000)
This book provides an introduction to the grammatical category of number, surveying many languages to reveal that the world's linguistic resources are richer than even many linguists realise. Aimed at linguistic students, it is the first book-length treatment of this topic and can serve as an entry to linguistic typology.